PROBLEMATIC OF CHILDREN DROPPED OUT OF SCHOOL IN DUWANUR VILLAGE, EAST FLORES - Ruswandi Mawar (SocioEdu: Sociological Education, 2021)
The research aimed to determine the cause of children drop out of school and to know parents’ efforts to cope with children dropping out of school in Duwanur Kecamatan Adonara Barat, Kabupaten Flores Timur, Nusa Tenggara Timur. This study used a qualitative method. The Subjects of this study were parents and children dropouts of school. The data collection technique used observation, interviews, and documentation. Data analysis techniques used data reduction, data display, and data verification. The results of this study indicate that the problems of children drop out of school in Duwanur were low economic, low interested, and low motivation to go to school.